A Knowledge Translation-Integrated Approach Evaluating the DREAM Program’s Webisodes and French Translation - Potter, Catherine (Université Saint-Paul / Saint Paul University, 2022)
The adverse effects of the COVID-19 lockdowns have led to mental health challenges in nearly three-quarters of Canadian children and youth. In this pilot evaluability assessment, we used a Knowledge Translation-Integrated approach to evaluate the credibility, acceptability, and sustainability of the school-based DREAM program at increasing resilience among children ages 7 to 11. Specifically, we assessed newly produced webisodes (meant to ease teacher administration) and the French translation of the program for the first time. Credibility was supported using quantitative measures for meaning mindset, mental illness symptoms, and COVID-19 coping. Knowledge users, in this case children and parents, were involved in measuring the DREAM program’s acceptability and sustainability qualitatively and quantitatively. Data was collected from 33 children, and 31 of their parents, who completed the program and the pre- and post-test questionnaires. The webisodes were found to be credible and acceptable to the children, and produced equivalent self-reported outcomes to the clinician-delivered classes at increasing meaning mindset, decreasing mental illness symptoms, and increasing COVID-19 coping. The French version of the program also produced equivalent self-reported outcomes to the English version at increasing meaning mindset, decreasing mental illness symptoms, and increasing COVID-19 coping. Validations and suggestions for the program were coded, grouped into themes, and analyzed. A discussion of the analyses is presented, including limitations and recommendations for future directions for further development of the DREAM program.
Keywords: psychoeducation, mental health, children, meaning mindset, covid-19, social emotional literacy